NEUROREHABILITATION ROBOTIC ARTIFICIAL INTELLIGENCE PLATFORM - Suraganov, Ayat; Kuanyshbaiuly, Mukhtar; Sagadiyeva, Aigerim (Nazarbayev University, Graduate School of Business, 2019)
Objective of the practicum project is to provide management and financial consulting to help improve performance and efficiency of the startup ReLive by First Project. ReLive is an innovative solution for the rehabilitation of patients after a stroke, which includes a device for reading electroencephalographical (EEG) signals, software for reading and recognition of EEG signals, microcontroller, and upper limbs exoskeleton. The practicum project was conducted by Bake partnership represented by Full time MBA students of Nazarbayev university. It involves quantitative and qualitative data, critical assessments of the project, risk analysis and financial forecast. The result of the practicum project involves key findings, recommendations and implementation plan for the company.
Keywords: Type of access: Restricted; EEG signals; startup ReLive; First Project